Inflammatory-Related Clinical and Metabolic Outcomes in COVID-19 Patients - Maria Martinez-Urbistondo; Alberto Mora-Vargas; Esther Expósito-Palomo; Raquel Castejón; M. Jesús Citores; Silvia Rosado; Carmen de Mendoza; Isolina Baños; Ana Fernández-Cruz; Lidia Daimiel; Rodrigo San-Cristóbal; Juan Antonio Vargas; et al. (Hindawi Limited, 2020)
Background. Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) infection elicits inflammatory manifestations that relate with a "cytokine storm." Objective. The aim of this research was to assess the role of circulating interleukin 6 (IL-6) levels and other inflammatory markers in patients with coronavirus disease 2019 (COVID-19) on metabolic functions and accompanying clinical complications. Patients and Methods. A total of 165 patients diagnosed with COVID-19 pneumonia were examined for medical features and inflammatory markers such as blood IL-6, CRP, ferritin, LDH, neutrophil/lymphocyte index (NLI), D-Dimer, and Red Cell Distribution Width (RDW). Regression analyses concerning electronically collected medical data were adjusted by appropriate factors and confounding variables. Results. Plasma IL-6 determinations evidenced a consistent association with hospital stay days, Intensive Care Unit (ICU) admission, and mortality rates. Similar trends were found for other proinflammatory variables, where ferritin and NLI showed a remarkable value as surrogates. Hyperglycaemia and the Charlson Comorbidity Index Score were positively associated with the inflammatory response induced by the SARS-COV-2 infection. An unhealthy lifestyle such as smoking and alcoholic drinks consumption as well as excessive body adiposity influenced inflammatory-related outcomes in the screened patients. Conclusion. IL-6 together with other inflammatory biomarkers accompanied poor clinical and metabolic outcomes in COVID-19-infected patients. IL-6 may result in a suitable proxy to individually categorise patients in order to manage this infectious pandemic.